Modelling and analysis of fiber Bragg grating temperature sensor for Internet of things applications (FBG-4-IoT) - Paul Stone Macheso; Mohssin Zekriti (International Journal of Intelligent Networks)
The integration of Fiber Bragg Grating (FBG) sensors into the Internet of Things (IoT) has garnered significant attention in recent years because of their immunity to electromagnetic and radio frequency interference, small size and weight, and corrosion resistance. This paper aims to enhance the performance characteristics of FBG sensors for temperature measurement by proposing a specific design of their parameters, thus facilitating their implementation in IoT applications. The FBG temperature sensor is designed to operate in the 1500–1600 nm wavelength range. The outcomes display a high sensitivity of 0.61 nm/°C with a Full Width Half Maxima (FWHM) of 7.893 nm and a Figure of Merit (FOM) of 7.72 x 10−2/°C. The calculated Quality Factor (Q) of the sensor was 195.67. When compared with previous studies in the literature, our obtained results confirm the enhanced performance of the proposed design of the FBG sensor, which render it suitable for utilization in most industrial use cases, especially in harsh environments.